2018
DOI: 10.18502/kss.v3i10.3371
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intellectual Capital on Business Performance in Micro-, Small-, and Medium Enterprise (MSME) in Medan City

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 5 publications
2
16
0
2
Order By: Relevance
“…0.000, it can be concluded that intellectual capital has a positive and significant effect on the performance of MSMEs. This is in line with research on intellectual capital in MSMEs conducted by (Dewi et al, 2019), (Absah et al, 2018), (Khalique et al, 2018) and (Supeno et al, 2015)…”
Section: Effect Intellectual Capital On Performances Of Msmesupporting
confidence: 89%
See 1 more Smart Citation
“…0.000, it can be concluded that intellectual capital has a positive and significant effect on the performance of MSMEs. This is in line with research on intellectual capital in MSMEs conducted by (Dewi et al, 2019), (Absah et al, 2018), (Khalique et al, 2018) and (Supeno et al, 2015)…”
Section: Effect Intellectual Capital On Performances Of Msmesupporting
confidence: 89%
“…Intellectual capital research indicates that intellectual capital developed in honing competent employees, innovating, and maintaining good relationships will result in successful businesses in the future and can excel in business competition between entrepreneurs in similar fields (Absah, Chairunisa Muchtar, and Qamariah, 2018).…”
Section: H2: Fintech Has a Positive Effect On Performance The Intelle...mentioning
confidence: 99%
“…The current studies have highlighted the inconsistency of previous research in which an indirect effects model, particularly the use of technology as a significant mediating variable in enhancing the sustainability of SMEs, was overlooked (Jämsä et al, 2011;Kim & Orazem, 2017;Zhong et al, 2020;Adam, 2021). There was also an inconsistency between intellectual capital and SMEs' performance (Absah et al, 2018;Maharani & Fuad, 2020;Ahmed et al, 2020;Mubarik et al, 2020). As a result, through technology, the intellectual capital component indirectly influences SMEs' sustainability.…”
Section: Introductionmentioning
confidence: 80%
“…More specifically, previous research has neglected identifying appropriate actions and strategies taken by leaders in times of crisis and the effectiveness of these strategies based on the company's capabilities (Bundy et al, 2016;Kunc & Bandahari, 2011), especially in terms of SME context (Appelbaum et al, 2012;Randall, 2018). Some researchers agree that intellectual capital components such as organizational capital, social capital, and human capital can add value to a company's goals (Khalique et al, 2013b;Absah et al, 2018;Nhon et al, 2018). Human capital, for example, with a level of education, experience, knowledge, social skills, innovation, and attitude in carrying out its work, will create value to achieve goals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation